INCREASE THE EXPORT POTENTIAL OF FREE ECONOMIC ZONES IN UZBEKISTAN - Goyibnazarova, Shakhnoza (Science technology&Digital finance, 2023)
This article mainly covers the concept of a free economic zone. In addition, information will be provided about the current state of Free Economic Zones in Uzbekistan, the activities of Free Economic Zones in China, the existing free economic and small industrial zones in Uzbekistan and the existing problems and shortcomings in this area, as well as achievements and benefits.